KADAR MALONDIALDEHID DAN AKTIVITAS ENZIM SUPEROKSIDA DISMUTASE PADA HIPERTENSI DAN NORMOTENSI: Malondialdehyde Level and Superoxide Dismutase Activity in Hypertensive and Normotensive - Dianti, Resti Rahma; Rusdi, Rusdi; Evriyani, Dian (Bioma, 2016)
Hypertension is a condition of high blood pressure caused by many factors. One of them is endothelial dysfunction indicated from malondialdehyde (MDA) level. The production of MDA is primarily prevented by endogenous antioxidant such as superoxide dismutase (SOD). This study aimed to identify the differences between level of MDA and the activity of SOD in hypertensive and normotensive. It also aimed to identify the correlation between MDA level and SOD activity in both group. This study was conducted in laboratory of animal physiology FMIPA UNJ on June to September 2015. This research used an Ex-Post facto method with a cross-sectional design. A total of 30 serum samples (N1 = N2 = 15) was examined to identify MDA level and SOD activity. Data of MDA level and SOD activity was analyzed by Mann-Whitney test and t-test, respectively. Correlation between MDA level and SOD activity was analyzed by Pearson Correlation test in normotensive group and by Spearman’s Rho test in hypertensive group. Based on the results, mean value MDA level in normotensive was 0,465±0,118 nmol/mL and in hypertensive is 1,279±0,307 nmol/mL. MDA level in normotensive was significantly different than hypertensive (Sig.=0,000). Mean value SOD activity in normotensive was 2,307±0,739 u/mL, and in hypertensive was 2,131±0,422 u/mL. SOD activity was not significantly different in normotensive and hypertensive (Sig.=0,432). In conclusion, there was no correlation between MDA level and SOD activity in hypertensive and normotensive group.